Pearce's surgical companion essential notes for postgraduate exams - Pearce, Oliver (Tfm Pub., 2009)
Presents a review of the subjects with which a junior doctor needs to be conversant in their postgraduate surgical exams in order to qualify as a specialist trainee. Written to aid the revision process, this work includes basic science, physiology, anatomy, examination techniques, operative surgery and clinical surgery topics.